STRATEGI RANTAI PASOKAN USAHA PENGGILINGAN PADI KABUPATEN MERAUKE - Anthonia Karolina Rejo Lobwaer (Universitas Musamus,Merauke,Papua, 2018)
The Rice Milling business continues to experience growth and places its position as the first supplier in the rice supply chain. This study aims to determine the activities of rice mills and their supply chain strategies. This research uses a descriptive qualitative. The results of the study found that there were 4 rice milling groups based on their activities, where 3 groups strengthened their position as the first channel with a backward integration strategy vertically so that they had control over suppliers / farmers. The independence of farmers and mutually beneficial partnerships is expected to provide balanced and reasonable benefits to each supply chain network